2019
DOI: 10.1177/2474126419858492
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Practice Preferences After Endophthalmitis Following Anti-VEGF Intravitreal Injection

Abstract: Purpose: This study examines treatment-based outcomes of endophthalmitis due to antivascular endothelial growth factor (anti-VEGF) intravitreal injection and its effect on subsequent management of neovascular disease. Methods: A retrospective multicenter study was conducted of 157 patients with a diagnosis of endophthalmitis following anti-VEGF intravitreal injection at 10 major ophthalmic centers. Results: The median number of injections before endophthalmitis was 10 (range, 1 to 84 injections). Initial treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…In our cohort, 30% of cases were culture positive, which was consistent with the range of 30% to 60% described in previous reports. 22,24 -27 Although culture-positive and culture-negative cases in our study did not significantly differ in VA at presentation or at 6 months, Xu et al have found in a larger cohort that culture-positive cases are more likely to have worse VA. 27…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…In our cohort, 30% of cases were culture positive, which was consistent with the range of 30% to 60% described in previous reports. 22,24 -27 Although culture-positive and culture-negative cases in our study did not significantly differ in VA at presentation or at 6 months, Xu et al have found in a larger cohort that culture-positive cases are more likely to have worse VA. 27…”
Section: Discussioncontrasting
confidence: 77%
“…In our cohort, 30% of cases were culture positive, which was consistent with the range of 30% to 60% described in previous reports. 22,[24][25][26][27] Although culture-positive and culture-negative cases in our study did not significantly differ in VA at presentation or at 6 months, Xu et al have found in a larger cohort that culture-positive cases are more likely to have worse VA. 27 As in other studies, 3,27,28 the most commonly isolated organism in our cohort was coagulase-negative Staphylococcus, with other cases growing S viridans, S maltophilia, and P acnes. Other studies have suggested that S viridans-associated endophthalmitis may be due to aerosol contamination from oral or respiratory flora during intravitreal injection and is often associated with a more severe clinical course.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…30 The culture-positive rate in various reports of postinjection endophthalmitis was lower than that in the EVS, ranging from 30% to 60%. 3,1922…”
Section: Sampling and Culturementioning
confidence: 99%